DESKRIPSI KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN MOTIVASI BELAJAR SISWA SMP NEGERI 1 SUMBANG - Lukmanul Akhsani; Puji Rahayu (AlphaMath : Journal of Mathematics Education, 2017)
This research aimed to describe students' mathematical creative thinking ability at SMPNegeri 1 Sumbang. This research belongs to descriptive qualitative research. The subjects ofthis research were the students Grade VII G of SMP Negeri 1 Sumbang. The samples weretaken using purposive sampling technique. The data were collected using questionnaire, test,interview, and documentation. The data validity test used in this research was triangulation.The results of this research illustrate that: 1) Low category students could meet one indicatorof mathematic creative thinking ability i.e. fluency. Their learning motivation was good. Theypreferred to learn in a group. They were enthusiastic when they were given awards during theinstruction. 2) Medium category students could meet two indicators of mathematic creativethinking ability i.e. fluency and flexibility. Their learning motivation was very good. Theywere active during the instruction and they preferred to work autonomously. They sometimesreviewed the lesson that had been learned at school. 3) High category students could mastermathematic creative thinking ability i.e. fluency and flexibility. Their learning motivation wasvery good. When they met hard questions, they would try to solve the problems well. Duringthe instruction, they were active and they preferred to work autonomously.KEY WORDS: Mathematical Creative Thinking, Learning Motivation